A Case Study of Malignant Edema in Postpartum Mediterranean Buffaloes (Bubalus bubalis) - D’Angelo, L.; Martucciello, A.; Marianelli, C.; Grassi, C.; Schiavo, L.; Armas, F.; Alfano, D.; Vecchio, D.; Carlo, E. De (Journal of Buffalo Science, 2020)
The paper describes for the first time four cases of postparturient malignant edema in water buffaloes due to Clostridium septicum (Cl. septicum). The study was carried out on four primiparous buffaloes that showed swelling of perineal and perivulvar areas, fever and agalactia a few hours after calving. Two of them died within 20 hours after calving. The other two developed edema in the skeletal muscles of one leg and were treated with sulfadiazine-trimethoprim for 10 days. The clinical signs completely resolved. Culture and molecular investigations identified the pathogen isolated from exudate taken from the vulva as Cl. septicum. The isolate showed multi-drug resistance. In the management of infection due to Cl. septicum, timely diagnosis and the chirurgic curettage, associated with a broad-spectrum antibiotic therapy, were found to be sufficient for the survival and recovery of the infected animals.